1998
DOI: 10.5465/amr.1998.926623
|View full text |Cite
|
Sign up to set email alerts
|

Between Trust and Control: Developing Confidence in Partner Cooperation in Alliances

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Academy of Management is collaborating with JSTOR to digitize, preserve and extend access to The Academy of Management Review.Strategic alliances have been recognized as arena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
1,565
4
70

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,186 publications
(1,664 citation statements)
references
References 95 publications
25
1,565
4
70
Order By: Relevance
“…Even if there is a long tradition of conceptualizing control and trust as alternatives (Knights et al 2001), the introduction of control systems does not necessarily imply a lowering of trust (Das and Teng 1998). A recent longitudinal empirical research study found that control can support and reinforce the development of trust in inter-organizational relationships (Vélez et al 2008).…”
Section: Research Questionsmentioning
confidence: 99%
“…Even if there is a long tradition of conceptualizing control and trust as alternatives (Knights et al 2001), the introduction of control systems does not necessarily imply a lowering of trust (Das and Teng 1998). A recent longitudinal empirical research study found that control can support and reinforce the development of trust in inter-organizational relationships (Vélez et al 2008).…”
Section: Research Questionsmentioning
confidence: 99%
“…Thus, Oxley and Sampson found that in some instances 'the choice of an equity joint venture encourages alliance partners to engage in joint activities that go beyond 'pure' R&D' (Oxley and Sampson 2004: 724). Equally, governance arrangements may also have relationship-inhibiting or even damaging effects, as where formal governance mechanisms are taken to signal distrust between parties (Das and Teng 1998). Similar considerations may arguably apply also to the influence of governance mechanisms upon knowledge processes.…”
Section: Developing Propositionsmentioning
confidence: 99%
“…The high rate of failure of alliances is attributed to a lack of cooperation and the opportunistic behavior of partners (Das and Teng, 1998). Minshall et al (2005) comment that in many instances the large firm is able to appropriate most of the value from the relationship and the general performance of the small firm may be adversely affected.…”
Section: Unintended Knowledge Flowsmentioning
confidence: 99%